POSSIBILITIES OF ARTIFICIAL INTELLIGENCE IN TEACHING THE COURSE: CHEMISTRY OF HOUSEHOLD MATERIALS - Pylypchuk , Liudmyla; Popovych , Tetiana; Reshnova , Svitlana; Volkova , Svitlana (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article presents the features of using digital technologies in the process of teaching the course «Chemistry of Household Materials». The advantages of using interactive tools, virtual laboratories, and online services are identified for the development of practical skills, enhancement of learners’ cognitive activity, and improvement of their digital competence.